Cinema panopticum - Ott, Thomas, 1966 June 10- (Seattle, WA : Fantagraphics Books, 2005)
Five interlinked wordless stories in graphic novel format.
-- The girl -- The hotel -- The champion -- The experiment -- The prophet.
Simultaneously published: Z?urich : Edition Moderne, 2005.
Keywords: Carnivals -- Comic books, strips, etc; Carnivals -- Fiction; Carnivals